Coupled double-distribution-function lattice Boltzmann model with streaming-collision process. Issue 1 (1st March 2023) - He, Zhuojie; Liang, Ruifang
Abstract: A coupled double distribution function lattice Boltzmann model with streaming-collision process is presented. In this model, continuity and momentum equations are recovered by a density distribution function and energy equation is recovered by a total energy distribution function, and the specific-heat ratio and Prandtl number are flexible. At the same time, the streaming-collision process is used as update rule. Couette flow is simulated as a numerical test. The numerical results agreed relatively excellent with the analytical solutions.